Forest cover dynamics in the Selva Maya of Central and Southern Quintana Roo, Mexico: deforestation or degradation?. Issue 1 (2nd January 2020) - Ellis, Edward A.; Navarro Martínez, A.; García Ortega, M.; Hernández Gómez, I. U.; Chacón Castillo, D.
ABSTRACT: Forest cover dynamics (1993-2018) was assessed in two regions on the Yucatan Peninsula: Zona Maya (ZM), 67% indigenous with shifting cultivation and community forestry; and Bacalar–Rio Hondo (BRH), mainly commercial agriculture and pastureland. Degradation (12, 915 ha y −1 ) exceeded deforestation (5882 ha y −1 ) and was worse in BRH. In BRH there was a net forest loss (−1.6% y −1 ) associated with pastureland and commercial agriculture. In ZM, mature forest recovery (1.4% y −1 ) and dynamic forest cover (continuous loss and gain) were associated with shifting cultivation. Changes were more intense during 2011–2018 and gains of mature forest in ZM and deforested areas in BRH targeted secondary vegetation. Fragments of mature and secondary vegetation decreased, and connectivity improved in ZM, but opposite trends occurred in BRH. Reporting and monitoring deforestation using Global Forest Watch data is inadequate since 62% of forest cover loss represent degrading or recovering forest cover.